The big sick [videorecording (DVD)] - Showalter, Michael, 1970-; Nanjiani, Kumail; Nanjiani, Kumail; Kazan, Zoe, 1983-; Romano, Ray (Lionsgate, 2017)
A couple struggles with their relationship when their parents disapprove due to cultural differences.